(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We developed a toilet-incorporated electric medical bed for bedridden patients, in which a toilet basin, or a commode, is incorporated in the pelvic plate of an electric medical bed. A replaceable toilet seat is located in the mattress of the bed, and toilet basin was tightly attached on the pelvic plate the bed. The excretion slides through a storage tube that angles toward the side of the bed and is automatically collected in a disposable plastic bag. We, however, encountered a problem with testing this newly developed medical bed with the relevant international standard IEC 60601-2-52:2009, or with the corresponding Korean standard KS P 0388:2012–Electrically operated adjustable bed for home care. There was no clear indication in the scopes of the above standards as to whether this standard testing method is applicable to an electric medical bed embedded with a commode. We revised the Korean standard KS P 0388:2012 to accommodate the toilet-incorporated medical bed in the scope of the standard and successfully performed the mechanical tests including the durability, impact, and deformation test of the bed, proving that the newly developed toilet-incorporated medical bed is mechanically strong and durable enough to pass the standard tests.